The Correlation between Critical Thinking Skill and Vocabulary Mastery in Critical Listening and Speaking Class - Vita Febia Pratiwi; Daniel Ari Widhiatama (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
The purpose of this research is to find out the relationship between students critical thinking and vocabulary mastery in Critical Listening and Speaking classes at a university in Yogyakarta. This research focused on knowing the relationship between students' critical thinking and vocabulary mastery of semester 4 students at a university in Yogyakarta. The population of this study were fourth semester students who were taking Critical Listening and Speaking courses. This research employed is quantitative design. In collecting data, researchers used questionnaires and tests. The research sample consisted of 15 students at an English Education Study Program. A vocabulary test using https://www.oxfordonlineenglish.com/english-level-test/vocabulary was used to investigate students’ vocabulary mastery. Meanwhile, a formative assignment was employed to gain students’ critical thinking level. To analyze the data, Pearson product moment correlation was used. The exploration discoveries show that there was a positive correlation between critical thinking skills and vocabulary mastery in CLS class with Sig. = 0.934. In this way, the alternative hypothesis (Ha) is acknowledged and null hypothesis (Ho) is dismissed. The importance of this assertion is a basic critical thinking skills impacts vocabulary mastery.